Blitzed eaudiobook - Martin, Alexa (The Playbook, 2019)
One of Buzzfeed's 16 Romantic Books To Read This Fall One of Popsugar's Best Books for Winter One of Refinery29's Best Books of December "Definitely a must-read!”—La La Anthony, New York Times bestselling author Maxwell Lewis has to make the play of his life in order to breach the woman of his dream’s defenses in this new football romance from the author of Fumbled .  Brynn Larson owes a lot to reality television and professional athletes. Her bar hit new heights of success after becoming a local haunt for the Denver Mustangs players and their WAGs. But although she’s grateful, that doesn’t mean she’s crazy. And that’s exactly what she would be to ever consider dating a professional athlete. Even if it’s Maxwell Lewis, whose shy smile makes her wonder what going on behind those beautiful brown eyes.  Maxwell knew from the moment he met Brynn that she was going to change his life. It was only a matter of time. But when he finally makes a move, fate conspires against him and everything goes wrong. Now he has to show her that their potential is real. Too bad for him, Brynn isn’t fooled by his glamorous NFL life, and when ghosts from both their pasts make a sudden reappearance, she must decide who she can trust. But when the person she’s most afraid of is herself, navigating life’s tackles is harder than anticipated.